Genetical and Morphological Identification of Prosthogonimus pellucidus (Digenea, Prosthogonimidae) in Grus japonensis - Yu Cao; Ye Li; Zhong-Yan Gao; Xian-Guang Zhang; Bo-Tao Jiang; Hong-Bao Wang (Biology)
Species of the family Prosthogonimidae are considered the most pathogenic trematodes of poultry and wild birds worldwide, causing heavy economic losses in many countries. Prosthogonimosis was a common parasitic disease of Grus japonensis (Müller, 1776) which caused inflammation of the cloaca and bursa of Fabricius and even death. Morphological identifications of Prosthogonimus species are easily confusing; therefore, molecular characterization is used for discrimination. The present study was conducted to identify Prosthogonimus species at Zhalong National Nature Reserve, northeast of China. Considering the morphological variability and wide host range of individual Prosthogonimus species, a combination of both morphological and molecular analyses is indispensable for the valid identification of this parasite and the internal transcribed spacer (ITS) region was amplified for the sequence analysis and phylogenetic analysis. The results of molecular analysis together with phylogenetic reconstruction indicated that the Prosthogonimus pellucidus (von Linstow, 1873) in this study form a single cluster with P. pellucidus, revealing potentially high diversity within the genus Prosthogonimus. Classification of Prosthogonimus species seems to be unrelated to the host and may be related to geographical location. These data provide a significant resource of molecular markers for studying the taxonomy, population genetics, and systematics of Prosthogonimidae.